Lisianthus cultivation using differentiated light transmission nets - Viegas Rodrigues, Paulo Hercilio; Martella, Julia; Calaboni, Cristiane (Ornamental Horticulture, 2016)
The Lisianthus stands out as one of the ten most cut flowers sold in the world. The use of meshes in a different light transmission is gaining more space in horticulture with promising results in greenhouse. The aim of this study was to evaluate the development of lisianthus grown in different light transmission meshes in blue, black, red and control treatments, which were transplanted 20 seedlings to cultivate Snow white with three replications, and therefore, 60 plants 240 plants per treatment in total. Agronomic characteristics such as plant height and length of the top pair of leaves were evaluated at 15, 38, 59, 82 and 105 days after transplanting. Other features such as early flowering, thick stem, distance between us and weight of the harvested stems were obtained at harvest stage. At the end of the evaluations, the treatment of red net was the most consistent with a significant difference in stem height and earliness in flowering.